THE ROLE OF SOCIAL MEDIA IN INFLUENCING INVESTMENT DECISIONS IN THE MILLENNIAL GENERATION - Hasanudin, Hasanudin (Jurnal Multidisiplin Sahombu, 2023)
The purpose of this research is to look into the influence of social media in influencing investment decisions among the millennial age. Because the millennial generation is thought to be the most reliant on digital technology and information, the influence of social media on them is growing. As a data gathering tool, this study employs quantitative methodologies with survey techniques. The research sample consists of 400 Bogor City millennials who use social media regularly. According to the study's findings, social media has a considerable influence on investment decisions among the millennial age. Based on these data, the study indicates that social media has a significant impact on millennial investment decisions. Therefore, investment companies and financial institutions need to consider using social media as a marketing and communication tool to attract the attention of the millennial generation and strengthen their brand image. In addition, the millennial generation needs to increase their self-awareness about investment risks and make investment decisions that are more rational and based on fundamental considerations.